Targeted Infarction of the Internal Capsule in the Rat Using Microstimulation Guidance. Issue 9 (September 2019) - Wen, Tong-Chun; Sindhurakar, Anil; Ramirez, Violeta Contreras; Park, HongGeun; Gupta, Disha; Carmel, Jason B.
Abstract : Background and Purpose—: Lacunar strokes are subcortical infarcts with small size and high disability rates, largely due to injury of the corticospinal tract in the internal capsule (IC). Current rodent models of lacunar infarcts are created based on stereotactic coordinates. We tested the hypothesis that better understanding of the somatotopy of the IC and guiding the lesion with electrical stimulation would allow a more accurate lesion to the forelimb axons of the IC. Methods—: We performed electrophysiological motor mapping and viral tracing to define the somatotopy of the IC of Sprague Dawley rats. For the lesion, we used an optrode, which contains an electrode to localize forelimb responses and an optical fiber to deliver light. The infarct was induced when light activated the photothrombotic agent Rose Bengal, which was administered systemically. Results—: We found largely a separate distribution of the forelimb and hindlimb axons in the IC, both by microstimulation mapping and tract tracing. Microstimulation-guided IC lesions ablated the forelimb axons of the IC in rats and caused lasting forelimb impairments while largely preserving the hindlimb axons of the IC and surrounding gray matter. Conclusions—: Stimulation guidance enabled selective and reproducible infarcts of the forelimb axons of the IC in rats. Abstract : Supplemental Digital Content is available in the text.